Convection-Enhanced Delivery In Silico Study for Brain Cancer Treatment - Lambride, Chryso; Vavourakis, Vasileios; Stylianopoulos, Triantafyllos (Frontiers in Bioengineering and Biotechnology, 2022)
Brain cancer therapy remains a formidable challenge in oncology. Convection-enhanced delivery (CED) is an innovative and promising local drug delivery method for the treatment of brain cancer, overcoming the challenges of the systemic delivery of drugs to the brain. To improve our understanding about CED efficacy and drug transport, we present an in silico methodology for brain cancer CED treatment simulation. To achieve this, a three-dimensional finite element biomechanics formulation is utilized which employs patient-specific brain model representation and is used to predict the drug deposition in CED regimes. The model encompasses nonlinear biomechanics and the transport of drugs in the brain parenchyma. Drug distribution was studied under various patho-physiological conditions of the tumor, in terms of tumor vessel wall pore size and tumor tissue hydraulic conductivity as well as for drugs of various sizes, spanning from small molecules to nanoparticles. Our contribution reports for the first time the impact of the size of the vascular wall pores and that of the therapeutic agent on drug distribution during and after CED. The in silico findings provide useful insights of the spatio-temporal distribution and average drug concentration in the tumor towards an effective treatment of brain cancer.